2019
DOI: 10.1002/ets2.12257
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Validity Evaluation of a Learning Progression for the Concept of Function

Abstract: Learning progressions (LPs) describe the development of domain‐specific knowledge, skills, and understanding. Each level of an LP characterizes a phase of student thinking en route to a target performance. The rationale behind LP development is to provide road maps that can be used to guide student thinking from one level to the next. The validity of an LP cannot be taken for granted, however. LPs evolve from a synthesis of multiple research studies, subject‐matter expertise, and standards documents. They are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Thus, the cognitive models constructed are regarded as a new theory of learning and cognition (Nichols et al, 2017) which has never been demonstrated to be valid (Nichols, 1994). In other words, the attributes associated with students' cognitive processes in solving the related tasks are only hypothesized by the experts (Graf et al, 2019). Thus, empirical evidence needs to be accumulated to verify the validity of the cognitive models constructed (Graf et al, 2019).…”
Section: Validity Of Cognitive Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the cognitive models constructed are regarded as a new theory of learning and cognition (Nichols et al, 2017) which has never been demonstrated to be valid (Nichols, 1994). In other words, the attributes associated with students' cognitive processes in solving the related tasks are only hypothesized by the experts (Graf et al, 2019). Thus, empirical evidence needs to be accumulated to verify the validity of the cognitive models constructed (Graf et al, 2019).…”
Section: Validity Of Cognitive Modelsmentioning
confidence: 99%
“…In other words, the attributes associated with students' cognitive processes in solving the related tasks are only hypothesized by the experts (Graf et al, 2019). Thus, empirical evidence needs to be accumulated to verify the validity of the cognitive models constructed (Graf et al, 2019).…”
Section: Validity Of Cognitive Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…(ETS, n.d., List Item 2)An LP identifies what Clements and Sarama (2004) have called “developmental progression[s] of levels of thinking” (p. 83). Each level of an LP “characterizes a phase of student thinking en route to target performance” (Graf et al, 2019, p. 1). The rationale behind LP development is to provide a map that can guide assessment design, instructional practice, and student learning (Graf et al, 2019).…”
mentioning
confidence: 99%
“…Each level of an LP “characterizes a phase of student thinking en route to target performance” (Graf et al, 2019, p. 1). The rationale behind LP development is to provide a map that can guide assessment design, instructional practice, and student learning (Graf et al, 2019). While LPs in related domains will have points of connection between them, thus creating networks of learning paths, the developmental levels are best understood by recognizing individual LPs belonging to individual domains (Daro et al, 2011).…”
mentioning
confidence: 99%